1994
DOI: 10.1038/369652a0
|View full text |Cite
|
Sign up to set email alerts
|

Virus-specific CD8+ T-cell memory determined by clonal burst size

Abstract: Although some viruses, particularly the herpes viruses, may never be eliminated from the body, others like influenza A, regularly reinfect humans and boost waning crossreactive CD8+ T-cell immunity. Prolonged T-cell memory is found for viruses that are unlikely to be re-encountered and which do not persist in the host genome, indicating that CD8+ T-cell memory might be independent of continued (or sporadic) antigenic exposure. A feature of virus-specific CD8+ T-cell memory is that antigen-specific cytotoxic T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
282
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(312 citation statements)
references
References 24 publications
28
282
1
1
Order By: Relevance
“…The CFSE dilution analyses described here indicated that increases in cell survival were likely to contribute significantly to the magnitude of the initial clonal T cell burst, which has been reported previously to predict the extent to which protective immunity is established [1]. However, the means by which TLR agonists promote T cell survival remain unclear.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The CFSE dilution analyses described here indicated that increases in cell survival were likely to contribute significantly to the magnitude of the initial clonal T cell burst, which has been reported previously to predict the extent to which protective immunity is established [1]. However, the means by which TLR agonists promote T cell survival remain unclear.…”
Section: Discussionsupporting
confidence: 68%
“…For example, the initial burst size of an anti-viral T cell response is correlated with long-term immunity [1], but unconstrained clonal expansion can lead to immunopathological effects [2]. Conversely, poor expansion or expansion in the absence of differentiation fails to establish immunity, and may even reinforce tolerance by generating cells with antigen-specific T regulatory function [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been obtained with replication competent WT HSV (data not shown). These data are in agreement with the notion that the amount of memory CTL is directly proportional to the clonal burst size of the corresponding primary response [14,15]. Together, our data indicate that CTL priming in DC-MHCI mice yields more effector and memory CTL as compared with C57BL/6 mice.…”
Section: Enhanced Ctl Clonal Expansion In the Absence Of Parenchymal supporting
confidence: 92%
“…This expansion is followed by a contraction phase when 90-95% of effector cells die by apoptosis and the surviving Ag-specific CD8 1 T cells form the memory T-cell pool. The resulting memory CD8 1 T-cell numbers are typically proportional to the peak in primary T-cell expansion [14,15] and elevated memory CD8 1 T-cell numbers can correlate with increased protection from re-infection [16,17]. Consequently, strategies to improve vaccines try to manipulate signals to optimize primary expansion of naïve CD8 1 T cells in order to generate the highest possible number of memory T cells.…”
Section: Introductionmentioning
confidence: 99%
“…T-cells are critical for controlling persisting noncytopathic viruses that hide in peripheral epithelial or mesenchymal cells and prevent them from re-emerging to trigger T-cell mediated immunopathological disease (Table 4). There is good evidence available now that these protective T-cells are also maintained by antigens [106,110,111], although this simple notion is very controversial at the present time [102,112,113]. Thus, low levels of ongoing T-cell responses reflect antigen-driven activated effector T-cells and not special memory T-cells.…”
Section: Consequences For Immunological Memorymentioning
confidence: 99%